The Complex Genetic Landscape of Hereditary Ataxias in Turkey and Implications in Clinical Practice - GÜNAL, DİLEK; AĞAN YILDIRIM, KADRİYE (WILEY, 2021)
Background The genetic and epidemiological features of hereditary ataxias have been reported in several populations; however, Turkey is still unexplored. Due to high consanguinity, recessive ataxias are more common in Turkey than in Western European populations. Objective To identify the prevalence and genetic structure of hereditary ataxias in the Turkish population. Methods Our cohort consisted of 1296 index cases and 324 affected family members. Polymerase chain reaction followed by Sanger sequencing or fragment analysis were performed to screen for the trinucleotide repeat expansions in families with a dominant inheritance pattern, as well as in sporadic cases. The expansion in the frataxin (FXN) gene was tested in all autosomal recessive cases and in sporadic cases with a compatible phenotype. Whole-exome sequencing was applied to 251 probands, selected based on the family history, age of onset, and phenotype. Results Mutations in known ataxia genes were identified in 30% of 1296 probands. Friedreich's ataxia was found to be the most common recessive ataxia in Turkey, followed by autosomal recessive spastic ataxia of Charlevoix-Saguenay. Spinocerebellar ataxia types 2 and 1 were the most common dominant ataxias. Whole-exome sequencing was performed in 251 probands with an approximate diagnostic yield of 50%. Forty-eight novel variants were found in a plethora of genes, suggesting a high heterogeneity. Variants of unknown significance were discussed in light of clinical data. Conclusion With the large sample size recruited across the country, we consider that our results provide an accurate picture of the frequency of hereditary ataxias in Turkey. (c) 2021 International Parkinson and Movement Disorder Society
Keywords: ataxia; genetics; heterogeneity; whole‐ exome sequencing; Turkey